P75 The role of mediastinoscopy in the post-EBUS world. (December 2018) - Jackson, A; Waqar, A; Griffiths, P; Brocklesby, C; Walshaw, M; Mohan, K
Abstract : Introduction: EBUS is widely used to investigate mediastinal lymphadenopathy and in many cases has subsumed the need for mediastinoscopy. We wished to determine the current role of mediastinoscopy in the investigation of mediastinal lymphadenopathy at our tertiary centre. Methods: We looked at the referral route, previous procedures, pathological results, final diagnosis, morbidity and mortality in all patients who underwent mediastinoscopy at our institution between 2015 and 2017. Results: There were 109 patients from 12 hospitals (median age of 61 [range 19 to 83], 57 [52%] male). 74 (68%) patients had previously undergone EBUS (twice in 4 cases), where a total of 96 nodes were sampled (reactive lymph node 30, granulomatous 14, non-diagnostic 17, suspicious for cancer and lymphoma 10, unable to obtain sample 3). Of the 30 reactive lymph nodes at EBUS, 15 were false negative at subsequent mediastinoscopy. Of the 35 (32%) direct referrals for mediastinoscopy, 18 (51%) were from respiratory clinicians. Overall reasons for referral were suspected Lymphoma 18, MDT decision 9, surgical decision 7 and patient choice 1. Of those with suspected lymphoma, only 5 had lymphoma at mediastinoscopy (28%). See table 1 for final diagnosis at mediastinoscopy. The median stay was 2 days and there was no mortality or major morbidity. Mediastinoscopy was non diagnostic in 3 (2.7%): of these 2 were subsequently referred for EBUS at our centre (1 lymphoma and 1 breast carcinoma). Conclusions: Our data show that patients are still being referred for mediastinoscopy directly from respiratory teams or after only one EBUS attempt, even when lymphoma is not suspected. We found large discrepancies in EBUS and mediastinoscopy pathology and suggest that a repeat EBUS procedure at an experienced centre be considered more readily prior to surgical referral.